Isolation and Identification of Bacterial Biosurfactant Activity from Mangrove Sediments - Sugihartuti, Rahmi; Pradana, Munawer; Maslachah, Lilik; Chusniati, Sri; Tyaningsih, Wiwiek; Rahardjo, Dadik; Soeharsono, Soeharsono (Journal of Basic Medical Veterinary, 2024)
Background: Ujung Pangkah mangroves are reported to have been contaminated with heavy metals. Such heavy metals can induce microorganisms to produce biosurfactants. Biosurfactants with amphiphilic characteristics can lower surface tension. Biosurfactants can be used as antibacterial, antifungal, and antiviral for biomedical purposes. Purpose: This study aimed to identify and test the activity of biosurfactant isolates of bacteria from Ujung Pangkah Mangrove sediments, Gresik Regency. Methods: Biosurfactant activity test methods include emulsification index, oil spreading, drop collapse, and parafilm test. Results: The results of the identification of bacterial isolates in this study obtained the genus Bacillus sp. because bacterial isolates show rod shape, Gram-positive, aerobic, and have ellipse-shaped endospores on the subterminal. The results of the biosurfactant activity test with the Emulsification index method showed an average result of 54.39% and the results of the biosurfactant activity test with the oil spreading method showed that there was a clear zone. The average result of the clear zone obtained is 54.83 mm. The average result in the parafilm test was 8.02 mm and the drop collapse test showed positive results characterized by falling and spreading of bacterial isolate fermentation broth supernatants.